Differential effects of perceived stress on alcohol consumption in moderate versus heavy drinking HIV-infected women. (1st September 2017) - Hutton, Heidi; Lesko, Catherine R.; Chander, Geetanjali; Lau, Bryan; Wand, Gary S.; McCaul, Mary E.
Highlights: Women with the human immunodeficiency virus (HIV) have high levels of perceived stress. Influence of stress on alcohol use depends on preexisting drinking patterns. Alcohol use increases with stress only if women were already heavy/binge drinkers. Alcohol use decreases with stress if women were already moderate drinkers. Following stress exposure, treatment should target subset of heavy drinkers. Abstract: Objective: To examine the association between perceived stress and subsequent alcohol use in women living with HIV. Methods: Women (n = 338) receiving HIV care between April 2006 and July 2010 who enrolled in either a brief intervention for hazardous drinking or a cohort of non-hazardous drinkers completed a 90-day drinking and drug use history, and completed stress, depression and anxiety measures at 0, 6, and 12 months. We examined the association between perceived stress at months 0 or 6 and measures of quantity and frequency of alcohol use in months 3-6 and 9-12, respectively. Results: The association between perceived stress and subsequent alcohol use depended on whether women were heavy or moderate drinkers at index visit. Among women reporting ≥7 drinks/week at index visit, high levels of perceived stress were associated with subsequent increased alcohol intake. However, among women reporting >0 but <7 drinks/week at index visit, high levels of perceived stress were associated with a subsequent reduction in drinking. Conclusions: Baseline drinking status moderates the relationship between perceived stress and subsequent alcohol use. Perceived stress is an important therapeutic target in women who are heavy drinkers.